Anthropometric and physical characteristics of U12-U18 basketball players at international and national level - Vadillo-Ventura, I.; Burgos-Postigo, S.; Fernández-Elias, E. V.; Montalvo-Pérez, A.; Navarro, R. M. (Deutsche Zeitschrift für Sportmedizin, 2025)
Objective: To describe the anthropometric and physical fitness parameters of young basketball players aged 12 to 18 years, as well as to assess differences between male and female players across different categories.